Linking globular cluster formation at low and high redshift through the age-metallicity relation in E-MOSAICS - Horta, Danny; Hughes, Meghan E; Pfeffer, Joel L; Bastian, Nate; Kruijssen, Diederik; Reina-Campos, Marta; Crain, Rob A (Monthly notices of the Royal Astronomical Society, 2021)
We set out to compare the age-metallicity relation (AMR) of massive clusters from Magellanic Cloud mass galaxies in the E-MOSAICS suite of numerical cosmological simulations with an amalgamation of observational data of massive clusters in the Large and Small Magellanic Clouds (LMC/SMC). We aim to test if: (i) star cluster formation proceeds according to universal physical processes, suggestive of a common formation mechanism for young-massive clusters (YMCs), intermediate-age clusters (IACs), and ancient globular clusters (GCs); (ii) massive clusters of all ages trace a continuous AMR; and (iii) the AMRs of smaller mass galaxies show a shallower relation when compared to more massive galaxies. Our results show that, within the uncertainties, the predicted AMRs of L/SMC-mass galaxies with similar star formation histories to the L/SMC follow the same relation as observations. We also find that the metallicity at which the AMR saturates increases with galaxy mass, which is also found for the field star AMRs. This suggests that relatively low-metallicity clusters can still form in dwarfs galaxies. Given our results, we suggest that ancient GCs share their formation mechanism with IACs and YMCs, in which GCs are the result of a universal process of star cluster formation during the early episodes of star formation in their host galaxies.
Published: 12 November 2020
Gesehen am 05.02.2021